Persepsi Mahasiswa terhadap E-Modul Pembelajaran Mata Kuliah Fisika Atom dan Inti - Haerul Pathoni; Jufrida Jufrida; Ika Saputri; Wulan Sari (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
Based on observations in atomic physics and nuclear learning, there are some problems see during two semester of the course such as less using of instructional materials and instructional media in the process of learning. In addition, content of book used are books published in the 1990s years and never have been updated. The quantity of books of atomic physics and nuclear in the library is still very little. Therefore developed electronic modul (E-modul). This research used descriptif research. E-module is made using 3D software pageflip professional. E-Module has been validated by experts for media and content of e-module. The result was perception of students on average 83.5% on core structure module and 89 % on radioactivity module with very good category.